2003
DOI: 10.1002/ajh.10371
|View full text |Cite
|
Sign up to set email alerts
|

Delayed introduction of G‐CSF after chemotherapy does not affect peripheral blood stem cell yield and engraftment kinetics in children with high‐risk malignancies: Retrospective study of 45 cases

Abstract: We retrospectively compared the effects of two time points of G-CSF (Filgrastim) introduction for PBSC mobilization in 45 children with different malignancies. Seventeen patients received the first G-CSF dose on day 2 or 3 following chemotherapy (group 1). Twenty-eight patients received a "flexible" G-CSF injection schedule when the G-GSF was started at the time of the first platelet count rise during post-chemotherapy recovery phase (group 2). Leukapheresis was performed when WBC recovery reached >2.0 × 10 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In previous reports, CD341 cell yields reached 6.7-6.8 3 10 6 /kg body weight [4,6], with a mean of 12-15 days of G-CSF treatment and a mean of 2-5.24 sessions of leukapheresis. The results of Dolgopolov [7] suggest that the G-CSF can be introduced at the time of initial WBC and platelet recovery in all patients without an adverse impact on the studied variables, rather than being introduced immediately after chemotherapy. The patients in this study achieved a yield of 6.1 3 10 6 CD341 cells/kg, with a mean of only 4 days of G-CSF treatment and a median of two sessions of leukapheresis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In previous reports, CD341 cell yields reached 6.7-6.8 3 10 6 /kg body weight [4,6], with a mean of 12-15 days of G-CSF treatment and a mean of 2-5.24 sessions of leukapheresis. The results of Dolgopolov [7] suggest that the G-CSF can be introduced at the time of initial WBC and platelet recovery in all patients without an adverse impact on the studied variables, rather than being introduced immediately after chemotherapy. The patients in this study achieved a yield of 6.1 3 10 6 CD341 cells/kg, with a mean of only 4 days of G-CSF treatment and a median of two sessions of leukapheresis.…”
Section: Discussionmentioning
confidence: 91%
“…Other centers start using G-CSF at the time of initial WBC or platelet recovery following mobilization [7]. In our earlier procedures for PBSC collection, G-CSF was first used at the point of the first peripheral WBC restoration (the first elevation of WBC count after nadir) following mobilization chemotherapy, according to Dolgopolov [7].…”
Section: Introductionmentioning
confidence: 99%
“…This approach, which implies no more than 5 days of growth factor therapy at most, has proven to be cost effective. 22,23 In this case, the cost of PEG is clearly higher and its use is apparently not justifiable from a solely financial point of view.…”
Section: Discussionmentioning
confidence: 97%
“…Their model showed no major differences in neutrophils engraftment time if the initiation of G-CSF was postponed for up to 5 days after transplantation. Dolgopolov I et al 16 reported a study of G-CSF-stimulated mobilization and harvest CD34+ cells in pediatric patients undergoing chemotherapy. They demonstrated that delayed administration of G-CSF targeted to the time of neutrophil reappearance in peripheral blood after chemotherapy was at least as effective as its "prefixed" start 24 hours after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%